The development concept of enhanced visualization-based augmented reality applications in education - Yusoff, Che Musazaki; Ghazali, Norliza; Sulaiman, Puteri Suhaiza; Wan Idris, Wan Mohd Rizhan; Abdul Hanid, Mohd Fadzil (Human Resource Management Academic Research Society, 2024)
This concept paper discusses the proposed design and development of augmented reality (AR) applications based on enhanced visualization. Previous development studies used marker-based techniques in developing applications. Development studies involving marker less techniques and three-dimensional (3D) object recognition in education are still understudied. This study will develop an application based on enhanced visualization through the use of 3D object recognition techniques. The theories and models underlying the study consist of constructivist learning theory, behaviourist learning theory, user experience (UX) design process models, and enhanced visualization. In order to evaluate the usability of the developed application, the UX component evaluation model is used. The design and development of AR applications using 3D object recognition techniques is expected to achieve the value of expert agreement through the Fuzzy Delphi method and provide a different experience to users through a more dynamic process without targeting two-dimensional (2D) images as markers while being able to meet the evaluation of UX components which includes product perception, consumer emotions, consequences of use and overall product evaluation.